The role of engagement, content, and understanding of numeracy literacy in physics creativity projects - Susilawati Susilawati; Andi Fadllan; Miftahida Pratama Mareta; Masturi Masturi; S Xaphakdy (Momentum: Physics Education Journal, 2025)
Pre-service physics teachers engagement and content material influence the strategies for implementing creative learning. Behavioural, emotional, cognitive, and reciprocal aspects are less visible during classroom learning. Content material can present several interesting topics that are more engaging if pre-service physics teachers s are directly involved through demonstrations, experiments, and learning in their surroundings. The approach aims to build interest and active engagement to complete project activities. The study seeks to determine whether project-based learning with active pre-service physics teachers engagement, content delivery, and numeracy literacy understanding can be enhanced through creative projects. The research uses a quasi-experimental design with control and experimental groups using pretest and post-test. A total of 39 pre-service physics teachers s were enrolled in this study, divided into two groups: the experimental group consisted of 21 pre-service physics teachers s who received instruction using the STEM-based creativity project method, and the control group consisted of 18 pre-service physics teachers s who received instruction using the inquiry and assignment method. Both classes were analysed based on pre-service physics teachers engagement, content material presentation, and numeracy literacy understanding. The study measured pre-service physics teachers performance before and after the intervention using tests. Pretest findings showed a p-value greater than 0.05 between the control and experimental groups, indicating no statistically significant difference between the two groups. A post-test showed a p-value of <0.001 between the groups, indicating that the experimental group significantly outperformed the control group. The findings of this study suggest that pre-service physics teachers engagement, content material packaging, and numeracy literacy understanding influence creative projects. This study supports the development of STEM-based creativity project learning and active pre-service physics teachers participation.